A multiplex real‐time PCR assay enables simultaneous rapid detection and quantification of bacteria associated with acute oak decline. (27th May 2020) - Crampton, Bridget G.; Plummer, Sarah J.; Kaczmarek, Maciej; McDonald, James E.; Denman, Sandra
Abstract: Acute oak decline (AOD) is a syndrome affecting mature oak trees and is characterized by stem bleeds from vertical fissures on trunks, and inner bark necrosis caused by a polybacterial consortium, in which Gibbsiella quercinecans and Brenneria goodwinii, and to a lesser extent Rahnella victoriana and Lonsdalea britannica, play key roles. Here we report a novel multiplex real‐time PCR assay that enables simultaneous and rapid detection and quantification of these four bacterial species from stem bleed swabs. Experiments with axenic cultures were performed to determine specificity and sensitivity of the multiplex quantitative PCR (qPCR). Whilst the primer/probe set for B . goodwinii was species‐specific, primer/probe sets for the other three species were able to identify other members of their respective genera. There was no cross detection of genera within the multiplex qPCR, and non‐target bacteria were not detected. The multiplex AOD assay had differential sensitivity for each bacterial species. The assay was evaluated on swab samples collected from stem bleeds of declining oak trees at a site in south‐east England and was able to detect all four bacterial species. Absolute quantification of the bacteria from swab samples was possible through the inclusion of a standard curve prepared from dilutions of gene copy standards. This diagnostic tool will facilitate rapid detection of AOD‐associated bacteria from samples that can easily be taken by non‐specialists without specific training, and will also find application in other experimental work such as pathogenicity and control trials. Abstract : The multiplex real‐time PCR assay can simultaneously detect four bacterial species associated with Acute Oak Decline (AOD) from stem bleed swabs, eliminating the need for destructive sampling of high‐value trees to isolate bacteria.